vectors

Asked by Rinkus | 2nd Aug, 2008, 02:29: PM

Expert Answer:

put l = -(m+n) in second equation.

you will get m2 + n2 +mn=0

this equation is quadratic in m so product of roots is m1m2 = - n2

similarly this equation is quadratic in n so product of roots is n1n2 = - m2


similarly replace m = -(l+n)  we will get   l2 + n2 +ln=0

so l1 l2 = - n2  and n1n2 = - l2

similarly replacing n = -(l+m)

we get   l1 l2 = - m2   and  m1m2 = - l2

now l1l2+m1m2+n1n2 = l2+m2+n2 = 0

i.e. angle between these lines are 90

Answered by  | 10th Aug, 2008, 02:58: PM

Queries asked on Sunday & after 7pm from Monday to Saturday will be answered after 12pm the next working day.